Entrepreneurial Motivation by Business Actors at Aeoropala Food Makassar City in terms of Entrepreneurship Education and Entrepreneurial Mentality - Fajriani Azis; Andika Isma (Pinisi Journal of Entrepreneurship Review, 2023)
This study aims to determine Entrepreneurial Motivation in Business Actors at Aeoropala Food Makassar City where entrepreneurship education and entrepreneurial mentality are one of the determining factors. The research is categorized as quantitative descriptive research with a population of 119 culinary entrepreneurs who are in Aeoropala Food Makassar City on Jalan Hesrtasning Makassar City. Data collection in this study was carried out using interview techniques, questionnaires, and documentation. The analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that entrepreneurship education is in a very high category which means an increase in knowledge and attitudes so as to increase motivation in entrepreneurship. Entrepreneurial Mentality is in a very high category which means an increase in risk-taking, and self-confidence. Entrepreneurial Motivation is in a very high category, which means that business actors in Aeoropala Food Makassar City have a high level of desire, hope, and encouragement in running their business. The results of this study indicate the effect of Entrepreneurship Education and Entrepreneurial Mentality simultaneously and significantly on the entrepreneurial motivation of Business Actors at Aeoropala Food Makassar City.